2017
DOI: 10.1007/s12529-017-9670-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical Behavior Profiles in Chronic Cancer-Related Fatigue

Abstract: PurposeIncreasing physical activity level is a generally effective intervention goal for patients who suffer from chronic cancer-related fatigue (CCRF). However, patients are unlikely to benefit equally from these interventions, as their behavioral starting points might vary substantially. Therefore, we explored patterns of physical behavior of participants who suffer from CCRF.MethodsBaseline data of a randomized controlled trial were used for a latent profile analysis on nine accelerometer-derived physical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 42 publications
3
26
1
Order By: Relevance
“…Some of the patients in our study spent relatively much time in moderate-to-vigorous activity, while at the same time accumulating considerable time in prolonged bouts of sedentary behavior; or vice versa. This supports the notion of individual variability, and emphasizes the need for so-called physical behavior 'profiling' to facilitate tailored goal setting in interventions that target change in physical behavior [14].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Some of the patients in our study spent relatively much time in moderate-to-vigorous activity, while at the same time accumulating considerable time in prolonged bouts of sedentary behavior; or vice versa. This supports the notion of individual variability, and emphasizes the need for so-called physical behavior 'profiling' to facilitate tailored goal setting in interventions that target change in physical behavior [14].…”
Section: Discussionsupporting
confidence: 60%
“…To investigate if preoperative and early postoperative physical behavior relates to health outcomes six months postoperative (t3), first Spearman's correlations were calculated between selected physical behavior measures preoperative and health outcomes at six months postoperative (t3), and between physical behavior measures at one month postoperative (t1) and health outcomes at six months postoperative (t3). To limit the number of tests, we calculated the association between the physical behavior measures PAL, SB, pSB, and MVPA, since their relevance in cancer rehabilitation has previously been reported [14]. Second, for pMVPA, patients were classified into three groups based on the international guidelines for PA in cancer survivors, that is a minimum of 150 min of MVPA per week [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first study to explore latent movement behavior profiles based on 24-h time-use compositions among a working population. Most similar previous studies (a) have been performed on children and adolescents [33][34][35][36] or (b) did not use 24-h data [37][38][39] or (c) did not use devicebased measures of movement behaviors [37,38]. We found that workers in this study could be divided into four distinct movement behavior profiles, that we named "Chimpanzees", "Lions", "Koalas", and "Ants".…”
Section: Discussionmentioning
confidence: 55%